Gender Differences and the Trend in the Acute Myocardial Infarction: A 10-Year Nationwide Population-Based Analysis - Hung-Yu Yang; Jen-Hung Huang; Chien-Yeh Hsu; Yi-Jen Chen (The Scientific World Journal)
It is not clear whether gender is associated with different hospitalization cost and lengths for acute myocardial infarction (AMI). We identified patients hospitalized for primary diagnosis of AMI with (STEMI) or without (NSTEMI) ST elevation from 1999 to 2008 through a national database containing 1,000,000 subjects. As compared to that in 1999~2000, total (0.35‰  versus 0.06‰, P<0.001) and male (0.59‰  versus 0.07‰, P<0.001) STEMI hospitalization percentages were decreased in 2007~2008, but female STEMI hospitalization percentages were not different from 1999 to 2008. However, NSTEMI hospitalization percentages were similar over the 10-year period. The hospitalization age for AMI, STEMI, and NSTEMI was increased over the 10-year period by 14, 9, and 7 years in male, and by 18, 18, and 21 years in female. The female and male hospitalization cost and lengths were similar in the period. As compared to nonmedical center, the hospitalization cost for STEMI in medical center was higher in male patients, but not in female patients, and the hospitalization cost for NSTEMI was higher in both male and female gender. We found significant differences between male and female, medical center and non-medical center, or STEMI and NSTEMI on medical care over the 10-year period.